Wpływ inflacji na integrację monetarną Polski w ramach struktur europejskich - Czarny, Marek (The Impact of Inflation on Poland's Monetary Integration within the Framework of the European Structures, 2006)
After Poland's accession to the European Union, the final stage of integration, i.e. joining the monetary union. was commenced. Realization of this stage of integration requires from Poland meeting convergence criteria set out in the Maastricht Treaty (including the inflation level, which, to a large extent, depends on proper monetary policy related to leveling off the interest rates, and on appropriate fiscal policy related to the budgetary discipline in terms of revenue and expenditure). It will be a difficult task, due to high external and domestic debt and the costs of integration, which will be on an upward trend in the upcoming years. The co-operation between the National Bank of Poland and the Ministry of Finance - two institutions, whose objectives in terms of the monetary and fiscal policy do not always converge- will be of great importance in this respect.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 142-149